2012
DOI: 10.1785/0120110089
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Dynamic Rupture Propagation beyond Fault Discontinuities: Effect of Thermal Pressurization

Abstract: A range of several fault segments often sequentially ruptures during an earthquake. We investigated the effects of thermal pressurization (TP) on dynamic rupture propagation beyond fault discontinuities by simulating spontaneous rupture propagation on two vertical strike-slip fault segments. We revealed that a rupture can jump wider stepovers owing to TP, and that TP on a primary (nucleating) fault enables a rupture to jump at deep portions. In previous numerical studies on dry fault systems, it was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Numerical simulations suggested that TP can increase the breakdown stress drop [e.g., Andrews , ; Bizzarri and Cocco , ], slip‐weakening distance [ Noda and Shimamoto , ; Rice , ], peak slip rate, and rupture velocity [ Bizzarri and Cocco , ; Urata et al ., , ]. Urata et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerical simulations suggested that TP can increase the breakdown stress drop [e.g., Andrews , ; Bizzarri and Cocco , ], slip‐weakening distance [ Noda and Shimamoto , ; Rice , ], peak slip rate, and rupture velocity [ Bizzarri and Cocco , ; Urata et al ., , ]. Urata et al .…”
Section: Introductionmentioning
confidence: 99%
“…[] showed that owing to TP, the slip‐weakening curves are different at different locations within a fault with uniform coefficients of friction and stress. TP and dynamic ruptures strongly depend on hydraulic diffusivity which is assumed to be constant over time and space [e.g., Bizzarri and Cocco , ; Urata et al ., , ]. Noda and Lapusta [] modeled earthquake cycles for the 1999 Chi‐Chi earthquake by two regions having different values of constant hydraulic diffusivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal pressurization is important when determining how a rupture evolves in a heterogeneous fault system. Urata et al [] showed that accounting for thermal pressurization allows a rupture to jump a wider step over; Noda and Lapusta [] showed that thermal pressurization can weaken rate‐strengthening sections of faults that would not normally slip seismically; Urata et al [] showed that the efficiency of thermal pressurization is an important consideration when determining if a rupture can branch.…”
Section: Introductionmentioning
confidence: 99%